Lithuanian priegaidė: a syllable or a word feature? - Aleksey Andronov (Vilnius University Open Series, 2022)
The place of priegaidė ‘syllable intonation’ in the phonological system of Lithuanian remains uncertain; so does its typological peculiarity. The article aims to discover the specific nature of this phonological feature taking into consideration the opposition between phonemic (inflectional) and syllabemic (isolating) language types. Phonetically similar prosodic means in these languages show noticeable functional differences determined by the structure of the meaningful units they belong to. Inflectional languages develop a system of suprasegmental phonological features, which integrate parts of their normally composite units, whereas isolating languages usually do with monosyllabic words (naturally, without stress) and monolithic morphemes with tones as distinctive features. Standard Lithuanian has priegaidė only on the stressed syllables, therefore its system can be called polyaccentual (not polytonic), i. e. possessing several types of accent. The dialects, however, show examples of relevant priegaidė besides syllables with primary stress. In this, more general, system priegaidė functions as a suprasegmental feature of a morpheme (exposed to fading in weak positions). The traditional differentiation of syllables according to priegaidė is secondary: a syllable provides conditions for the realization of priegaidė, but being part of the plane of expression, not connected with meaning, the syllable itself does not need differentiation.